Bea Martínez, M. y Lanau Hernáez, P. (coordinadores) (2021). Corpus del Arte Rupestre del Alto Aragón. IEA/Diputación Provincial de Huesca. Huesca. (Salduie, 2022)
Se reseña la obra de Bea y Lanau "Corpus del Arte rupestre del Alto Aragón".